Infrastructure and Innovation: Rethinking Digital Literacy for K-12 Learners - Irvani, Asep Irvan; Anisah, Ani Siti; Masripah (Sinergi International Journal of Education, 2024)
In the wake of accelerating digital transformation, this study investigates how digital infrastructure, competency frameworks, and policy implementation influence digital literacy in K-12 education. The study employs a narrative review methodology, synthesizing findings from diverse literature databases including Scopus, Web of Science, and Google Scholar. Using keywords such as "digital literacy," "K-12," "ICT integration," and "teacher digital competence," studies were screened based on inclusion criteria focusing on infrastructure, pedagogy, and policy. The review reveals that access to robust digital infrastructure significantly correlates with enhanced student engagement and digital skill acquisition. Countries with well-developed digital ecosystems exhibit stronger outcomes due to government investment, teacher training, and integrated curricular reforms. In contrast, developing countries face persistent challenges such as unequal infrastructure distribution, policy misalignment, and limited professional development opportunities. Notably, the study challenges the assumption that individual resistance is the primary barrier, emphasizing instead the structural nature of these obstacles. Recommendations include strengthening policy frameworks, increasing investment in rural connectivity, and implementing scalable teacher training programs. The study underscores the necessity for adaptive, data-driven, and equity-oriented interventions to close the digital divide and promote inclusive educational transformation. The findings offer strategic insights for policymakers, educators, and researchers seeking to build resilient digital learning environments.